2020
DOI: 10.1016/s0735-1097(20)31579-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Treatment in Heart Failure With Preserved Ejection Fraction: A Systematic Review and Meta Regression Analysis

Abstract: Background: Observational series suggest a mortality benefit from metformin in the heart failure (HF) population. However, the benefit of metformin in HF with preserved ejection fraction (HFpEF) has yet to be explored. We performed a systematic review and meta-analysis to identify whether variation in EF impacts mortality outcomes in HF patients treated with metformin. Methods: MEDLINE and EMBASE were searched up to October 2019. Observational studies and randomised trials reporting mortality in HF patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, treatment reducing nutrient overload might be beneficial and should be preferred. Metformin, for example, which has shown beneficial effect on mortality in HF patients [ 49 ], although often referred to as insulin sensitizer, has its main glucose-lowering effect via reducing hepatic glucose production. Similarly, SGLT-2 inhibitors lower blood glucose by promoting glycosuria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, treatment reducing nutrient overload might be beneficial and should be preferred. Metformin, for example, which has shown beneficial effect on mortality in HF patients [ 49 ], although often referred to as insulin sensitizer, has its main glucose-lowering effect via reducing hepatic glucose production. Similarly, SGLT-2 inhibitors lower blood glucose by promoting glycosuria.…”
Section: Discussionmentioning
confidence: 99%
“…Strong pathogenic links have emerged between diabetes and HF with preserved ejection fraction (HFpEF) [41]. A meta-analysis of four studies in patients with T2D and HFpEF demonstrated a significant reduction in mortality with metformin, especially for those with LVEF > 50% [42]. A recent retrospective study of patients with type 2 diabetes and HFpEF demonstrated reduced mortality associated with metformin only in patients with sub-optimal glycaemic control (HbA1c ≥ 7%) [43].…”
Section: Clinical Outcomes Following Metformin Treatment In People Wi...mentioning
confidence: 99%
“…HFpEF, in particular, is regarded increasingly as a hitherto under recognised cardiovascular complication of diabetes, and is associated with a severely adverse prognosis [41]. The EMPEROR Preserved trial [130] recently identified a SGLT2 inhibitor as the first pharmacologic intervention to improve hard clinical outcomes in this populationthe suggestion of improved outcomes in metformin-treated patients with HFpEF from a metaanalysis [42] and retrospective studies [43,44], described above, merits further study.…”
Section: How Do We Interpret the Evidence Base For Metformin Today?mentioning
confidence: 99%
“…A more recent meta-analysis by Halabi et al that specifically investigated all-cause mortality in diabetic patients with heart failure did stratify results according to HFrEF and HFpEF [12]. In this meta-analysis, which pooled data of 22,469 patients from four observational studies (including three that were also included by Crowley et al), metformin reduced allcause mortality in patients with HFpEF (β = -2.3 (95% CI -3.3 to -1.3)) but not HFrEF (β = 0.2 (95% CI -0.2 to 0.6)).…”
Section: The Era Before Cardiovascular Outcome Trialsmentioning
confidence: 99%